Copper molybdenum sulfide anchored nickel foam: a high performance, binder-free, negative electrode for supercapacitors. Issue 29 (11th July 2018) - Sahoo, Surjit; Krishnamoorthy, Karthikeyan; Pazhamalai, Parthiban; Kim, Sang -Jae
Abstract : A novel negative electrode based on copper molybdenum sulfide (CMS) nanostructures prepared through a facile method for supercapacitor applications. Abstract : Herein, we are demonstrating the use of a binder-free electrode based on copper–molybdenum–sulfide nanostructures grown on nickel foam (CMS/Ni) as a novel negative electrode for supercapacitors. The cyclic voltammetry and charge–discharge analyses reveal the pseudocapacitive nature of the CMS/Ni electrode with a high specific capacity of 633 mAh g −1 (∼20-fold higher than the binder-based CMS electrode) which is mainly due to their superior electronic conductivity and short ion transport pathways. Furthermore, the fabricated symmetric supercapacitor using the CMS/Ni electrode delivered a high device capacitance (265.62 F g −1 ), high energy density (23.61 Wh kg −1 ) and long cycle-life. The results ensure that the CMS/Ni binder-free electrode will be a promising negative electrode for high-performance supercapacitors.